CircRNA circ_0006677 Inhibits the Progression and Glycolysis in Non–Small-Cell Lung Cancer by Sponging miR-578 and Regulating SOCS2 Expression - Yang, Bo; Zhao, Fang; Yao, Lei; Zong, Zhenfeng; Xiao, Li (Frontiers in Pharmacology, 2021)
Objective: Circular RNAs (circRNAs) have been demonstrated in playing an important role in the physiological and pathological processes (such as cancer). This paper aims to clarify the role of Circ_0006677 in non-small cell lung cancer (NSCLC) progression. Methods: Using clinical data and in vitro cell line models, we revealed the tumor-suppressive role of circ_000667 in lung cancer. Using the online bioinformatics tool, we predicted the target of circ_0006677 and further validated its regulatory mechanisms responsible for its tumor suppressor function in NSCLC. Results: Circ_0006677 expression is reduced in NSCLC tissues of patients and lung cancer cells in comparison to adjacent normal tissues. Lower expression of circ_0006677 is significantly associated with poorer patient survival. Overexpression of circ_0006677 significantly inhibits the ability of NSCLC cell proliferation, migration, invasion and glycolysis. Mechanically, circ_0006677 could inhibit NSCLC progression and glycolysis by regulating the expression of signal transducer inhibitor SOSC2 through sponging microRNA-578 (miR-578). Conclusions: Circ_0006677 prevents the progression of NSCLC via modulating the miR-578/SOSC2 axis.